Uses of Coir Fibre, its Products, & Utilization of Geo-Coir in India - G., Nagaraja; Basavaiah, C. (Indian Journal of Marketing, 2011)
Coir is a natural fibre that's extracted from the Coconut husk, and it's popularly known as "The Golden Fibre", composed of highly lignified form of cellulose. All coir fibre falls into two distinctly different categories viz. white coir and brown coir-the differences between two categories are due to the conditions of husk used, the method of extraction, the physical properties as well as in the uses. Brown coir is used in floor mats and Mat Brush Mattress, floor tiles and sacking. A small amount is also made into Twine. Pads of curled brown coir fibre, made by needle-felting (a machine technique that mats the fibres together) are shaped and cut to fill mattresses and for use in erosion control on river banks and hillsides. A major proportion of brown coir pads are sprayed with rubber Latex which bonds the fibres together (rubberised coir) to be used as upholstery padding for the automobile industry in Europe. The material is also used for Thermal insulation and packaging. The major use of white coir is in Rope manufacture. Mats of woven coir fibre are made from the finer grades of bristle and white fibre using hand or mechanical looms. White coir also used to make fishing nets due to its strong resilience to salt water. In coir is a strongly recommended substitute for because it is free of Bacterium and Fungus spore, and produces good results without the Natural environment damage caused by peat mining. Coir is also useful to deter snail from delicate plantings. Coconut coir from Mexico has been found to contain large numbers of colonies of the beneficial fungus Aspergillus terreus, which acts as a biological control against plant pathogenic fungi. Total production of Coir Fibre in the world 3, 50,000 tones. In India, 4,10,000 million tones of fibre were produced during 2005-06. Kerala produces 60 percent of the world's supply of White Fibre, Sri Lanka produces 36 percent of world Brown fibre output. Geo-coir are made of pure coir drawn from the husk of the coconut without adding any synthetic material - a cent percent natural product. The whole thing can be expressed as geo-textile. A large amount of coir fibres can be collected, processed & used in India.